Do cognitive schema mediate the association between childhood trauma and being at ultra-high risk for psychosis?. (May 2017) - Appiah-Kusi, E.; Fisher, H.L.; Petros, N.; Wilson, R.; Mondelli, V.; Garety, P.A.; Mcguire, P.; Bhattacharyya, S.
Abstract: Exposure to childhood trauma has been associated with psychotic symptoms, being at ultra-high risk for psychosis (UHR), and psychotic disorders such as schizophrenia. Negative self-beliefs have been shown to partially mediate the relationship between childhood trauma and paranoia and have been shown to be characteristic of patients with psychosis. However, whether the association between childhood trauma and being at high risk of developing psychosis (e.g., UHR) and paranoia symptoms is mediated by altered cognitive schema is unknown and warrants investigation to inform preventive interventions. Data was collected on 30 UHR patients from Outreach and Support in South London about exposure to childhood trauma, cognitive schema, paranoia and cannabis use. Relative to healthy controls (n = 38), UHR patients were significantly more likely to report exposure to various types of childhood trauma (emotional and sexual abuse, and emotional and physical neglect), had more negative schema and less positive schema about themselves and others, and were more likely to use cannabis more than once a month. Emotional neglect was found to be significantly associated with UHR status even after controlling for the effects of previous exposure to cannabis use (b = 0.262, 95% CI: 0.115–0.408), and this association was partially mediated by negative self-schema (b = 0.045, 95% CI: 0.004–0.159). Similarly, emotional neglect was significantly associated with paranoia (b = 1.354, 95% CI: 0.246-2.462), and this association was partially mediated by negative self-schema (b = 0.988, 95% CI: 0.323-1.895). These findings provide preliminary evidence about the cognitive mechanisms that may underlie the association between childhood trauma and later risk for psychosis.